Ceramics from Villa El Salvador, a late formative site from the Central Coast of Perú - Delgado, Mercedes (2007)
We applied a multielemental analytical method for characterization of archaeological ceramics from Villa El Salvador. The ceramics were characterize using Instrumental Neutron Activation Analyses (INAA), Energy-Dispersive X-ray Fluorescence (EDXRF) and X-ray Diffraction (XRD) techniques. Whole vessels with no accurate provenience and Villa El Salvador ceramics sherds were analyzed. The EDXRF system can measure both the whole vessels and ceramics sherds. The results from the whole vessels were in good agreement with the results obtained from the ceramics sherds, with one exception. Thus, the comparison of the EDXRF spectra of the whole vessels with the data base of the Villa El Salvador sherd collection allows us the identification of distinctive groups of the site.